Shyness and Its Relationship to Some Variables among Kindergarten Children (Journal Of Educational and Psychological Researches, 2025)
The current research aims to examine shyness in relation to some variables among kindergarten children. To achieve this, a scale of 15 items was developed by the researcher to measure shyness; it was administered to 150 kindergarten children who were selected randomly from different kindergartens at the Al-Karkh side of Baghdad Governorate. The researcher adopted an integrative framework of theories. The results of the research showed kindergarten children have a high level of shyness. There are no significant differences in terms of shyness between females and males and social skills. Finally, there are significant differences in the methods of treatment of the democratic style and increased protection.